Co-epidemics: implications of COVID-19 outbreak associated with human immune-deficiency virus, tuberculosis and Lassa fever in a low resource economy-a call for proactive measures - Osho P. Olanrewaju; Osho E. Omosalewa; Okoro, Lawrence; Ojo-Rowland Olawale (International Journal Of Community Medicine And Public Health, 2023)
As the global struggle to combat the quadruple burden of COVID-19, human immunodeficiency virus, tuberculosis and Lassa fever continues to increase, Sub-Saharan Africa has been the most affected region, especially Nigeria. There is a close interaction between these four diseases and a clear understanding of each of these diseases is very crucial. People living with chronic medical conditions such as HIV, TB and Lassa fever are more likely to experience poor outcomes from COVID-19 even though there are still some unknown facts as regards the burden of COVID-19 on patients with TB, Lassa fever and HIV in our low-middle–income nation. This study was conducted to review different researches on COVID-19 associated with HIV, TB and Lassa fever co-infections, to understand the interactions between them and its implications on clinical investigations and health management in high burden countries of COVID-19, especially Nigeria. The research was designed to accommodate research and reports from different geopolitical zones of Nigeria where the diseases has been reported and centering on Ondo State reports. This was done using search engines, with reference to valid studies from academic sources like ResearchGate, PubMed and Google Scholar. We also evaluated various related titles, abstracts and full reports for eligibility. Ondo state was the centre of study as it is one of the states with high prevalence of Lassa fever, TB, HIV and COVID-19 co-infections in Nigeria. Structured diagnostic algorithms and clinical management are suggested to improve COVID-19/HIV/TB/Lassa fever or COVID-19/Lassa fever co-infection outcomes. With low quality of health care facilities for laboratory diagnosis of COVID-19 and Lassa fever, reliance on clinical acumen and high index of suspicion may be the only process that health professionals may rely upon to make early diagnosis.